2021
DOI: 10.48550/arxiv.2112.01051
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Magnetic correction to the Anomalous Magnetic Moment of Electron

Fan Lin,
Mei Huang

Abstract: We investigate the leading order correction of anomalous magnetic moment (AMM) to the electron in weak magnetic field and find that the magnetic correction is negative and magnetic field dependent, indicating a magnetic catalysis effect for the electron gas. In the laboratory to measure the g − 2, the magnitude of the magnetic field B is several T, correspondingly the magnetic correction to the AMM of electron/muon is around 10 −34 /10 −42 , therefore the magnetic correction can be safely neglected in current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…Once the temperature increases and exceeds the critical point T c , κ decreases and turns to zero implying dynamical AMM disappears while the chiral symmetry restores. In [57], the AMM of electron under magnetic field has been calculated and it was shown that it is proportional to the m 2 , therefore, we can extend it to QCD as κ = vσ 2 with v = 2.30.…”
Section: B Anomalous Magnetic Moment Inducing Spin Polarizationmentioning
confidence: 97%
See 1 more Smart Citation
“…Once the temperature increases and exceeds the critical point T c , κ decreases and turns to zero implying dynamical AMM disappears while the chiral symmetry restores. In [57], the AMM of electron under magnetic field has been calculated and it was shown that it is proportional to the m 2 , therefore, we can extend it to QCD as κ = vσ 2 with v = 2.30.…”
Section: B Anomalous Magnetic Moment Inducing Spin Polarizationmentioning
confidence: 97%
“…However, the AMM of electron under external magnetic field has been calculated in Ref. [57], and the result shows a magnetic dependent AMM, which motivates us to study the magnetic dependent AMM effect on properties of magnetized quark matter and hadron.…”
Section: Introductionmentioning
confidence: 99%